Tracking empowerment along the value chain: Testing a modified WEAI in the Feed the Future Zone of Influence in Bangladesh - Ahmed, Akhter; Malapit, Hazel J.; Pereira, Audrey; Quisumbing, Agnes R.; Rubin, Deborah; Ghostlaw, Julie; Haque, Md. Latiful; Hossain, Nusrat Zaitun; Tauseef, Salauddin (International Food Policy Research Institute, 2018)
Upon request of the U.S. Agency for International Development (USAID), the International Food Policy Research Institute (IFPRI) conducted this study to support USAID in assessing the state of empowerment and gender parity of men and women along the agricultural value chain in the Feed the Future (FTF) Zone of Influence (ZOI) in Bangladesh. Specifically, IFPRI’s Policy Research and Strategy Support Program (PRSSP), funded by USAID, piloted the modified Women’s Empowerment in Agriculture Index (WEAI) survey instruments in 10 upazilas (sub-districts) within the FTF ZOI across 1,200 households, which broadly belong to three economic activities of interest: (1) agricultural production, (2) agricultural entrepreneurship, and (3) agricultural sector employment. The quantitative survey was complemented by qualitative research to glean further insights into the facilitators and constraints of empowerment among various actors in the agricultural value chain. The data and analysis generated from this WEAI for Value Chain (WEAI4VC) study may inform USAID’s selection and design of interventions that may, in turn, maximize its programmatic impact on women and men’s empowerment as producers, entrepreneurs, and wage employees.